Euthanasia: Damaged Wildlife and the Role and Duties of a Wildlife Rehabilitator - Parker, Kip (Wildlife Rehabilitation Bulletin, 2011)
Wildlife rehabilitators still sometimes struggle to articulate and create policies around their role and responsibilities within the profession, especially where euthanasia and the humane end to suffering is concerned. This article provides additional discussion for the ongoing dialogue on the role of euthanasia in wildlife rehabilitation and how rehabilitators should strive to meet these responsibilities, based on the principles of best science and best available care.